Gene expression profiling after exposure to a chemical carcinogen, Pentabrominated Diphenyl Ether, at different life stages - Shockley, Keith R.; Dunnick, June K. (Frontiers in Toxicology, 2023)
Exposure to environmental hazards occurs at different stages of our lifetime – infant, child, adult. This study integrates recently published toxicogenomics data to examine how exposure to a known rat chemical carcinogen (pentabrominated diphenyl ether (PBDE)) upregulated liver transcriptomic changes at different life cycle stages (PND 4, PND 22, adult). We found that at all three life cycle stages PBDE exposure induced hepatocellular transcriptomic changes in disease pathways including cancer, metabolic, membrane function, and Nrf2 antioxidant pathways, pathways all characteristics of chemical carcinogens. In addition, in the adult rat after a five-day exposure to the chemical carcinogen, there was upregulation of members of the Ras oncogenic pathway, a specific pathway found to be activated in the PBDE-induced tumors in rats in a previous hazard identification cancer study. The findings of liver transcript changes characteristic of carcinogenic activity after early life exposures and after short-term adult exposures provides data to support the use of transcriptomic data to predict the apical cancer endpoints in model studies. Using data from gene expression profiling studies after neonatal, young, or adult short-term chemical exposure helps to meet the 21st century toxicology goal of developing study designs to reduce, refine, and replace the use of traditional two-year rodent cancer studies to provide hazard identification information. The studies reported here find that key transcripts associated with carcinogenesis were elevated in neonate (PND 4), young (PND 22) and adult animals after short-term exposure to PBDE, a known experimental chemical carcinogen in model systems.